EXAMINATION OF THE SUSTAINABLE CONSUMPTION BEHAVIOURS OF WOMEN AND MEN FROM DIFFERENT GENERATIONS (Third Sector Social Economic Review, 2019)
This study was planned for the purpose of examining the sustainable consumption behaviours of women and men from different generations and it was conducted in Çankaya district of Ankara with 519 individuals selected by simple random sampling using a survey technique. The “Sustainable Consumption Behaviour Scale” developed by Doğan, Bulut and Çımrın (2015) that consists of 17 items and 4 sub-dimensions was used in the second part to measure sustainable consumption behaviours. While no statistically significant difference was found between the sustainable consumption behaviours of the individuals who participated in the study and their gender. A statistically significant difference was found between the generations. It was found that the silent generation, baby boomers and generation X exhibited higher sustainable consumption behavior than generation Y and generation Z. Also, generation Y exhibited higher sustainable consumption behavior than generation Z. Furthermore, a statistically significant difference was found between sustainable consumption behaviours of women and men from baby boomers and Z generation. The results showed that that male and female participants exhibited different consumption behaviors according to the generations. The implications of these findings are discussed and gave suggestions to individuals, related institutions and organizations in terms of adopting sustainable consumption behaviors.
Keywords: Generation; gender; sustainable consumption; sustainable consumption behaviour